2014
DOI: 10.1007/s00248-014-0489-z
|View full text |Cite|
|
Sign up to set email alerts
|

Biodegradation of Dichlorodiphenyltrichloroethanes (DDTs) and Hexachlorocyclohexanes (HCHs) with Plant and Nutrients and Their Effects on the Microbial Ecological Kinetics

Abstract: Four pilot-scale test mesocosms were conducted for the remediation of organochlorine pesticides (OCPs)-contaminated aged soil. The results indicate that the effects on degradation of hexachlorocyclohexanes (HCHs) and dichlorodiphenyltrichloroethanes (DDTs) were in the following order: nutrients/plant bioaugmentation (81.18 % for HCHs; 85.4 % for DDTs) > nutrients bioaugmentation > plant bioaugmentation > only adding water > control, and nutrients/plant bioaugmentation greatly enhanced the degradation of HCHs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 72 publications
(75 reference statements)
0
4
0
1
Order By: Relevance
“…Humic acids can increase the apparent solubility of DDT (Carter and Suffet 1982 ), but amending the soil with high quantities of organic matter was found to significantly retard DDT biodegradation, possibly due to binding of DDT to dissolved organic carbon (Kantachote et al 2004 ). Further research on the complex interactions between soil physical–chemical properties, its microbiome, including the microbial functional degradation potential, and the crops’ physiological contribution to the soil environment in relation to the possibilities to degrade DDT is thus needed to understand the behaviour of DDT residues (Sun et al 2015 ), particularly under climate change conditions (Gaur et al 2018 ). However, even though seasonal variation in DDT concentrations has been reported in soils (Zhang et al 2013 ), in agreement with the finding of differential release of residues into atmosphere (Motelay-Massei et al 2005 ; Liu et al 2009 ), sampling consistently at the end of summer during our monitoring exercise should have also reduced the risk of a bias in the results due to seasonal variability.…”
Section: Resultsmentioning
confidence: 99%
“…Humic acids can increase the apparent solubility of DDT (Carter and Suffet 1982 ), but amending the soil with high quantities of organic matter was found to significantly retard DDT biodegradation, possibly due to binding of DDT to dissolved organic carbon (Kantachote et al 2004 ). Further research on the complex interactions between soil physical–chemical properties, its microbiome, including the microbial functional degradation potential, and the crops’ physiological contribution to the soil environment in relation to the possibilities to degrade DDT is thus needed to understand the behaviour of DDT residues (Sun et al 2015 ), particularly under climate change conditions (Gaur et al 2018 ). However, even though seasonal variation in DDT concentrations has been reported in soils (Zhang et al 2013 ), in agreement with the finding of differential release of residues into atmosphere (Motelay-Massei et al 2005 ; Liu et al 2009 ), sampling consistently at the end of summer during our monitoring exercise should have also reduced the risk of a bias in the results due to seasonal variability.…”
Section: Resultsmentioning
confidence: 99%
“…The natural attenuation therefore often takes years or even decades to occur. Bioaugmentation [5,9] and biostimulation [10], aiming at the addition of exogenous degrading strains or growth substrates, respectively, are viewed as cost-effective and environmentally friendly methods for organic pollution mitigation at industrial sites [11]. These two strategies could significantly improve the existence or activities of PCP degraders, and further accelerate PCP bioremediation.…”
Section: Page 17 "mentioning
confidence: 99%
“…In recent years, bioremediation procedures have focused on phytoextraction and phytoremediation to clean up soils contaminated with organic pollutants as polycyclic aromatic hydrocarbons (PAHs) and POPs [ 15 , 16 ]. Recent studies have demonstrated the importance of understanding the relationship between bacterial activity generated by the plant and remediation process of contaminated soil with DDTs and HCHs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%